Anti-mattering mediates the relationship between social-responsibility misalignments and mental health problems in young people - Gooding, Patricia; Kort, Karolina Kluk-de; Ramsdale-Capper, Piers; Epton, Tracy (Frontiers in Psychiatry, 2025)
Background/objectivesMental health problems among university students are increasing in prevalence, and it is vital to understand why. The detrimental effects of misalignments between corporate social-responsibility values and those of employees have been widely evidenced. We investigated how misalignments between the personal importance of social-responsibility values held by students versus those of their university affected their mental health. It was predicted that anti-mattering would mediate relationships between misalignments in social-responsibility values and mental health problems.MethodsStudent participants (N=171) completed an online survey assessing the personal importance of nine social-responsibility domains together with the perceived importance of these domains to the student’s university. Participants also completed a measure of anti-mattering which assesses perceptions of being insignificant and invisible, and a composite measure of depression-anxiety-stress. Direct and indirect pathways were assessed with linear regression models.ResultsThere were four key findings. First, across the nine social-responsibility domains, personal importance ratings were significantly higher than those ascribed to the university. Second, misalignments in social-responsibility importance ratings were significantly associated with depression-anxiety-stress scores. Third, the relationship between the discrepancy in social-responsibility importance ratings and depression-anxiety-stress was mediated by anti-mattering. Fourth, the key characteristic of anti-mattering in this mediated pathway was perceived invisibility.ConclusionThere is potential for a positive effect on mental health to be gained if institutions, such as universities, authentically co-develop, instantiate, and evaluate social-responsibility values with stakeholders in ways that genuinely combat invisibility, and instead, reflect that the views and feelings of stakeholders do matter.